Red cell alloimmunization is associated with development of autoantibodies and increased red cell transfusion requirements in myelodysplastic syndrome - Deepak Singhal; Monika M. Kutyna; Rakchha Chhetri; Li Yan A. Wee; Sophia Hague; Lakshmi Nath; Shriram V. Nath; Romi Sinha; Nicholas Wickham; Ian D. Lewis; David M. Ross; Peter G. Bardy; et al. (Haematologica, 2017)
Up to 90% of patients with a myelodysplastic syndrome require red blood cell transfusion; nevertheless, comprehensive data on red cell alloimmunization in such patients are limited. This study evaluates the incidence and clinical impact of red cell alloimmunization in a large cohort of patients with myelodysplastic syndrome registered in the statewide South Australian-MDS registry. The median age of the 817 patients studied was 73 years, and 66% were male. The cumulative incidence of alloimmunization was 11%. Disease-modifying therapy was associated with a lower risk of alloimmunization while alloimmunization was significantly higher in patients with a revised International Prognostic Scoring System classification of Very Low, Low or Intermediate risk compared to those with a High or Very High risk (P=0.03). Alloantibodies were most commonly directed against antigens in the Rh (54%) and Kell (24%) systems. Multiple alloantibodies were present in 49% of alloimmunized patients. Although 73% of alloimmunized patients developed alloantibodies during the period in which they received their first 20 red cell units, the total number of units transfused was significantly higher in alloimmunized patients than in non-alloimmunized patients (90±100 versus 30±52; P